STAGES OF UPBRINGING AND DEVELOPMENT OF SPEECH-IMPAIRED CHILDREN IN THE FAMILY - Makhmudova Madinakhan; Rozmatova Odinakhan (Journals Park Publishing, 2023)
It is very important to cooperate with the family and help them in the implementation of work to eliminate, correct and develop children with speech defects. This article contains practical thoughts about the above issues and the stages of family upbringing and development of speech-impaired children.
Keywords: Speech-impaired children, mental functions, parents, family environment, individual program, speech development, speech, cognitive activity.